2022
DOI: 10.1057/s41599-022-01372-5
|View full text |Cite
|
Sign up to set email alerts
|

Exchange rate response to economic policy uncertainty: evidence beyond asymmetry

Abstract: Recent studies have examined the relationship between economic policy uncertainty and exchange rate. We contribute to this literature by considering the effect of minor positive and major positive changes as well as minor negative and major negative changes in the economic policy uncertainties on the exchange rates. In this regard, we use a recently developed multiple asymmetric threshold nonlinear ARDL model along with Granger causality in quantile test. Our estimates support the asymmetric effect in three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 48 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…Moreover, the findings related to the control variables indicate that, excluding research and development intensity, the remaining control variables significantly affect carbon emissions [ 42 , 43 ]. also introduced the control variables in their research conducted in the US, UK, and other developed countries to consider the fixed effects.…”
Section: Results Discussionmentioning
confidence: 99%
“…Moreover, the findings related to the control variables indicate that, excluding research and development intensity, the remaining control variables significantly affect carbon emissions [ 42 , 43 ]. also introduced the control variables in their research conducted in the US, UK, and other developed countries to consider the fixed effects.…”
Section: Results Discussionmentioning
confidence: 99%
“…Based on the works of Chang et al ( 2022 ), Music et al ( 2022 ), Popkova ( 2022 ), Popkova and Sergi ( 2021 , 2022 ), Rezapour et al ( 2022 ), Romano et al ( 2022 ), Sergi and Popkova ( 2022 ), which note the financial benefits of corporate social responsibility, this research hypothesizes (H 1 ) that the humanization (qualitative criterion) of workplace organization provides more of an increase in e-commerce business revenue than an increase in the number (quantitative criterion) of jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Accounting for linear model weaknesses, Chang et al (2022) employed nonlinear method and identified a significant effect of economic policy uncertainty for all sample countries' exchange rates, which varies across different quantiles. El-Abed et al (2022) concluded that domestic economic policy uncertainty has an asymmetric effect on China and Japan exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the theoretical relationship, the scant empirical literature examining the impact of economic policy uncertainty focuses on exchange rate fluctuations in levels (Abid, 2019;Chang et al 2022;El-Abed et al 2022;Kido, 2016;Kurasawa, 2016;and Murad, 2022 among others) and exchange rate volatility (Abid and Rault, 2021;Balcilar et al 2015;among others). Exchange rate changes in levels and volatility have a negative impact on domestic macroeconomic indicators.…”
Section: Introductionmentioning
confidence: 99%